Genetisk variation i säsongsbunden reproduktion hos får - Bonow, Sandra (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2011)
The purpose of this literature study was to describe the seasonal reproduction in sheep and the presence of genetic variation in fertility traits. Methods to induce oestrus are described and the possibilities to change the reproduction season through breeding are discussed. Sheep have a pronounced seasonality in their reproduction. Mating season starts in the fall and the lambs are born during the spring because this is the most beneficial time. The market request for lamb meat has increased and therefore it is desirable with ewes that could get pregnant all year round. The reproduction season is mainly controlled by the photoperiod and breeds from high latitudes are more seasonal than breeds that origin from the equator. Reproduction season can be artificially controlled by light programs or with hormone treatment, but in a long-term perspective the best strategy is to change the animals genetically, through controlled breeding, to make them less sensitive to the photoperiod. Heritability for fertility traits is low, but there is genetic variation in these traits which make selection possible. Nevertheless it has seemed difficult to make the animals completely aseasonal. Through breeding it would however still be possible to shorten the anoestrus period and improve spring fertility and thus make the lamb production less seasonal.